A genetic toolkit for tagging intronic MiMIC containing genes. - Nagarkar-Jaiswal, S.; DeLuca, S.Z.; Lee, P.T.; Lin, W.W.; Pan, H.; Zuo, Z.; Lv, J.; Spradling, A.C.; Bellen, H.J. (eLife, 2015)
Previously, we described a large collection of Minos-Mediated Integration Cassettes (MiMICs) that contain two phiC31 recombinase target sites and allow the generation of a new exon that encodes a protein tag when the MiMIC is inserted in a codon intron (Nagarkar-Jaiswal et al., 2015). These modified genes permit numerous applications including assessment of protein expression pattern, identification of protein interaction partners by immunoprecipitation followed by mass spec, and reversible removal of the tagged protein in any tissue. At present, these conversions remain time and labor-intensive as they require embryos to be injected with plasmid DNA containing the exon tag. In this study, we describe a simple and reliable genetic strategy to tag genes/proteins that contain MiMIC insertions using an integrated exon encoding GFP flanked by FRT sequences. We document the efficiency and tag 60 mostly uncharacterized genes.